Role of golimumab, a TNF-alpha inhibitor, in the treatment of the psoriatic arthritis - Michelon, Melissa A (Dove Medical Press, 2010)
Psoriatic arthritis (PsA) is an inflammatory arthritis that affects many psoriasis patients and can often have a debilitating disease progression. Golimumab is a new tumor necrosis factor (TNF) antagonist recently approved by the FDA for controlling signs and symptoms of psoriatic arthritis. In a Phase III clinical trial in patients with PsA, patients receiving golimumab showed significant improvement in the signs and symptoms of disease. It was usually well tolerated, but adverse events generally occurred more in patients receiving golimumab compared to placebo. Golimumab has also recently shown efficacy in slowing structural damage in PsA. This new biologic therapy provides physicians with another option in the treatment of this inflammatory arthritis while offering patients certain advantages over other TNF antagonists.